Effects of resisted sprint training on acceleration in professional Rugby Union players - West, D. J.; Cunningham, D. J.; Bracken, R. M.; Bevan, H. R.; Crewther, B. T.; Cook, C. J.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2013)
The use of weighted sled towing as a training tool to improve athlete acceleration has received considerable attention; however, its effectiveness for developing acceleration is equivocal. This study compared the effects of combined weighted sled towing and sprint training against traditional sprint training on 10 and 30 m speed in professional rugby union players (n = 20). After baseline testing of 10 and 30 m speed, participants were assigned to either the combined sled towing and sprint training (SLED) or traditional sprint training (TRAD) groups, matched for 10-m sprint times. Each group completed 2 training sessions per week for 6 weeks, with performance reassessed post-training. Both training programmes improved participants' 10 and 30 m speed (p < 0.001), but the performance changes (from pre to post) in 10 m (SLED -0.04 ± 0.01 vs. TRAD -0.02 ± 0.01 seconds; p < 0.001) and 30 m (SLED -0.10 ± 0.03 vs. TRAD -0.05 ± 0.03 seconds; p = 0.003) sprint times were significantly greater in the SLED training group. Similarly, the percent change within the SLED group for the 10 m (SLED -2.43 ± 0.67 vs. TRAD -1.06 ± 0.80 seconds; p = 0.003) and 30 m (SLED -2.46 ± 0.63 vs. TRAD -1.15 ± 0.72 seconds; p = 0.003) tests were greater than the TRAD group. In conclusion, sprint training alone or combined with weighted sled towing can improve 10 and 30 m sprint times; however, the latter training method promoted greater improvements in a group of professional rugby players.